Role of Maternal Infections and Inflammatory Responses on Craniofacial Development - Bhagirath, Anjali Y.; Medapati, Manoj Reddy; de Jesus, Vivianne Cruz; Yadav, Sneha; Hinton, Martha; Dakshinamurti, Shyamala; Atukorallaya, Devi (Frontiers in Oral Health, 2021)
Pregnancy is a tightly regulated immunological state. Mild environmental perturbations can affect the developing fetus significantly. Infections can elicit severe immunological cascades in the mother's body as well as the developing fetus. Maternal infections and resulting inflammatory responses can mediate epigenetic changes in the fetal genome, depending on the developmental stage. The craniofacial development begins at the early stages of embryogenesis. In this review, we will discuss the immunology of pregnancy and its responsive mechanisms on maternal infections. Further, we will also discuss the epigenetic effects of pathogens, their metabolites and resulting inflammatory responses on the fetus with a special focus on craniofacial development. Understanding the pathophysiological mechanisms of infections and dysregulated inflammatory responses during prenatal development could provide better insights into the origins of craniofacial birth defects.